Pathogenesis of pupillary capture after posterior chamber intraocular lens implantation. Issue 12 (December 1986) - Lavin, M.; Jagger, J.
Abstract : Pupillary capture is an unusual complication of posterior chamber intraocular lens implantation and may occur in the early or late postoperative period. We describe a series of patients with early or late onset pupillary capture and describe the pathogenesis. Early capture results from mechanical factors and is usually preventable. Late capture may be mechanical but is usually a sequel to the formation and subsequent contraction of iridocapsular synechiae. Synechiae result from lens epithelial or iris stromal hyperplasia and myofibroblastic metaplasia; they may be minimised by an atraumatic technique and adequate control of postoperative inflammation. The effect of pupillary capture is largely cosmetic, and we encountered no specific complications attributable to it.